2021
DOI: 10.3390/ijerph182010603
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning to Identify Interaction of Single-Nucleotide Polymorphisms as a Risk Factor for Chronic Drug-Induced Liver Injury

Abstract: Drug-induced liver injury (DILI) is a major cause of drug development failure and drug withdrawal from the market after approval. The identification of human risk factors associated with susceptibility to DILI is of paramount importance. Increasing evidence suggests that genetic variants may lead to inter-individual differences in drug response; however, individual single-nucleotide polymorphisms (SNPs) usually have limited power to predict human phenotypes such as DILI. In this study, we aim to identify appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The results showed that 1184 combinations and strategies achieved the highest fitness function value of 99.99. Conversely, when SNPS are randomly combined, there is a one in two [ 6 ] chance that the calculated result is the highest fitness function value, which is substantially lower than the value achieved using our mined results. These findings suggest there is a robust correlation between the mined SNP combinations, strategies, and paclitaxel clearance, and also underscore the efficacy of the GEP‐CSI data mining algorithm.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The results showed that 1184 combinations and strategies achieved the highest fitness function value of 99.99. Conversely, when SNPS are randomly combined, there is a one in two [ 6 ] chance that the calculated result is the highest fitness function value, which is substantially lower than the value achieved using our mined results. These findings suggest there is a robust correlation between the mined SNP combinations, strategies, and paclitaxel clearance, and also underscore the efficacy of the GEP‐CSI data mining algorithm.…”
Section: Resultsmentioning
confidence: 69%
“…Such integration can elucidate the possible influences of SNPs on a phenotype, thereby refining the precision of the analysis. However, alternative techniques such as machine‐learning algorithms may offer a robust mechanism to discern intricate interplays between variables [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria set out to specifically predict DILI, as diagnosed by liver biopsy, was met by one study which utilized genomics data. The study by Moore et al employed three ML algorithms, multivariate adaptive regression splines (MARS), multifactor dimensionality reduction (MDR), and LR, with the aim of investigating single-nucleotide polymorphisms (SNPs) (Moore et al, 2021 ). The effect of SNP-SNP interactions on DILI susceptibility as well as their ability to predict DILI chronicity were observed.…”
Section: Discussionmentioning
confidence: 99%